2015
DOI: 10.1371/journal.pone.0120590
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of Cold Tolerance at the Germination and Booting Stages in Rice by Association Mapping

Abstract: Low temperature affects the rice plants at all stages of growth. It can cause severe seedling injury and male sterility resulting in severe yield losses. Using a mini core collection of 174 Chinese rice accessions and 273 SSR markers we investigated cold tolerance at the germination and booting stages, as well as the underlying genetic bases, by association mapping. Two distinct populations, corresponding to subspecies indica and japonica showed evident differences in cold tolerance and its genetic basis. Both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(81 citation statements)
references
References 32 publications
(34 reference statements)
3
78
0
Order By: Relevance
“…Consistent with a previous study (Pan et al 2015), we found that both temperate and tropical japonica cultivars are more tolerant to cold stress than the IND and AUS cultivars (Fig. 1 and Additional file 1: Table S1).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Consistent with a previous study (Pan et al 2015), we found that both temperate and tropical japonica cultivars are more tolerant to cold stress than the IND and AUS cultivars (Fig. 1 and Additional file 1: Table S1).…”
Section: Discussionsupporting
confidence: 92%
“…Although Pan et al (2015) and Fujino et al (2015) recently reported the association mapping of cold tolerance QTLs in rice, the low resolution of SSR marker genotyping data affects the interval distance of the mapped QTLs. In this study, we mapped 67 QTLs associated with CTS in 295 rice accessions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…17 QTLs related to rice germinability at low temperature were detected by a GWAS analysis with the population of 63 rice varieties from Japan (Fujino et al 2015). Pan et al (2015) mapped 51 QTLs for cold tolerance at the germination and booting stages using a population of 174 Chinese rice varieties. Lv et al (2016) detected 132 QTL for nature chilling and cold-shock tolerance at the seedling stage by a GWAS analysis of 527 rice cultivars.…”
Section: Introductionmentioning
confidence: 99%